2013
DOI: 10.1080/02757540.2013.810724
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation trends of metals and a metalloid in the freshwater crayfishAstacus leptodactylusfrom Lake Yeniçağa (Turkey)

Abstract: We define the accumulated Gouy phase shift as the on-axis phase accumulated by a Gaussian beam in passing through an optical system, in excess of the phase accumulated by a plane wave. We give an expression for the accumulated Gouy phase shift in terms of the parameters of the system through which the beam propagates. This quantity complements the beam diameter and the wave-front radius of curvature to constitute three parameters that uniquely characterize the beam with respect to a reference point in the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 54 publications
(22 reference statements)
3
8
0
Order By: Relevance
“…This is the strongest correlation seen in non-gill tissues, and has also been reported in previous studies (e.g. by Nakayama et al on Cherax quadricarinatus and Tunca et al on A. leptodactylus [30,40]). The hepatopancreas is a major site of heavy metal sequestration in crustaceans, and metallothioneins are one of the most prominent metal sequestrating protein families.…”
Section: Discussionsupporting
confidence: 89%
“…This is the strongest correlation seen in non-gill tissues, and has also been reported in previous studies (e.g. by Nakayama et al on Cherax quadricarinatus and Tunca et al on A. leptodactylus [30,40]). The hepatopancreas is a major site of heavy metal sequestration in crustaceans, and metallothioneins are one of the most prominent metal sequestrating protein families.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, it was observed that Al was the most accumulated metal among the tested metals. Previous studies also supported our result (Tunca et al 2013a, Fikirdeşici-Ergen et al 2015. Mn is one of the essential metal and it was shown that crayfish has potential to gathered high amounts of Mn (Tunca et al 2012) Al-Mn corellations were found perfectly in the hepatopancreas and the muscle (r=1.000).…”
Section: Discussionsupporting
confidence: 89%
“…With digestive system, by inhalation, or skin contact, heavy metals may penetrate crustaceans' tissues. Penetration and accumulation of heavy metals in the tissues may cause some debilitating chronic discomfort (Tunca et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Cu is essential for all known organisms and serves as the cofactor for many different enzymes (Franco et al, 2009). It even enters the structure of the hemocyanin, the oxygen carrier protein, in the crustaceans (Tunca et al, 2013a, b). Cu can cause stomach, intestinal, liver, kidney and anemia diseases.…”
Section: Resultsmentioning
confidence: 99%
“…No data appeared to be normally distributed. On this, nonparametric Kruskal Wallis and Mann-Whitney U tests were preferred in the comparison of the averages (Tunca et al, 2013a).…”
Section: Comparison Of Quantity Difference Betweenmentioning
confidence: 99%